2010
DOI: 10.1016/j.jml.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Superficial priming in episodic recognition

Abstract: We explored the effect of superficial priming in episodic recognition and found it to be different from the effect of semantic priming in episodic recognition. Participants made recognition judgments to pairs of items, with each pair consisting of a prime item and a test item. Correct positive responses to the test item were impeded if the prime and test item were superficially related; this was the case when the items were words and the crucial relationship was phonological and orthographic as well as when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…Although the basic manipulation of Experiment 1 was the same as for Dopkins et al (2010a), previous work suggested that the familiarity representation for the experiment would be more likely to record perceptual information than the familiarity representation of Dopkins et al Whereas perceptual relatedness had no effect on the false-alarm rate for Dopkins et al, perceptual relatedness increased the false-alarm rate in Experiment 1. These results suggest that the familiarity representation for the experiment recorded perceptual information.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the basic manipulation of Experiment 1 was the same as for Dopkins et al (2010a), previous work suggested that the familiarity representation for the experiment would be more likely to record perceptual information than the familiarity representation of Dopkins et al Whereas perceptual relatedness had no effect on the false-alarm rate for Dopkins et al, perceptual relatedness increased the false-alarm rate in Experiment 1. These results suggest that the familiarity representation for the experiment recorded perceptual information.…”
Section: Discussionmentioning
confidence: 99%
“…The goal was to show that the false-alarm rate to the test word was greater in the Related than the Unrelated condition. On the basis of the results of Dopkins et al (2010a), we also expected the hit rate to be lower in the Related than the Unrelated condition. This result, which will be discussed later, was not of primary interest.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations